Time-segmented Physical Activity Patterns of Brazilian Adolescents: Within- and Between-day Variability. Issue 2 (3rd April 2023) - Lopes, Marcus V. V.; da Costa, Bruno G. G.; Malheiros, Luís E. A.; Carvalho, Humberto M.; Crochemore-Silva, Inácio; Silva, Kelly S.
ABSTRACT: This study examined the within- and between-day variability of time-segmented sedentary behavior (SB), light physical activity (LPA), and moderate-to-vigorous physical activity (MVPA) in adolescents. The sample comprised 154 adolescents (11–16 years old) from two public schools in Florianópolis, Brazil. The proportion of time spent in SB, LPA, and MVPA was measured using Actigraph GT3X+ accelerometers for the following weekday time segments: before school (07:00–07:59), school time (08:00–11:59), after school (12:00–12:59), afternoons (13:00–17:59), and evenings (18:00–23:00). Participants were more active during commuting-related time segments. Females showed lower MVPA than males during school time, afternoons, and evenings, but not before school and after school. Higher age was associated with higher SB and lower LPA during school time, afternoons, and evenings, and slightly lower MVPA during afternoons. The variability of SB, LPA, and MVPA for all time segments was mainly explained by within-participant day-to-day variations rather than between-participant differences of daily-averaged estimates.